TI_GERICHTE 52.2022.252 vom 9. August 2022 , Commesse pubbliche. Conformità dell'offerta. Criteri di idoneità - TI Tribunale d'appello (2022)
Commesse pubbliche. Conformità dell'offerta. Criteri di idoneità